Fish diversity and protein content analysis of traditional Lao fish The boundary of the Xe-Champhone River Champhone District Savannakhet Province - Sootkongthong, Koonphet; Boutxakittilath, Sounantha; Ladsavong, Phouvisai; Praxaysombath, Bounthob; Kongmany, Santi (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Fish diversity and the nutritional value of traditional Lao fish are necessary because they are an important challenge to development both in terms of conservation and food security. The purpose of this research is to create basic information about the nutritional composition of fish and the diversity of fish species found in the area of the Xe-Champhone River in Savannakhet Province, which has been surveyed and fish samples collected in the upstream, midstream, and downstream areas of Xe-Champhone in Champhone District. Fish samples were characterized by morphological characteristics with biological techniques as well as analyzed for proteins in some fish meat by using the Kjeldahl method. Research results found that: 14 families of fish include 44 species. The most family is Cyprinidae 41%; followed by the fish is Bagridae 11%; Cobitidae 9%; Balitoridae 7%; Mastacembelidae 7%; Tetraodontidae 7% of the fish families; The less family are Cobiidae, Siluridae, Synbranchidae, Brlonidae, Channidae, Anabantidae, Nandidae and Ambassidae with 2% of the fish families. The fish diversity index during the dry season is H'=0.30 and the rainy season is H'=0.40, which shows that the diversity of the species is low, indicating that the water resources are low in abundance. From the comparison of the fish species diversity in each sampling point according to the season, it can be found that: fish species during the rainy season are more than during the dry season is 58.46% and 42.54% respectively. Among them, Cyprinidae has the highest species with 13-17 species, followed by Bagridae is 3-5 species and Cobitidae with 2-4 species. The remaining 11 families are small in number. From the analysis of the amount of protein in fish (% Protein) it was found that: Monopterus albus (Synbranchidae) has the highest protein content of 27.7%, followed by the fish is Noedontobutis aurarmus (Gobiidae) of 22%, Thai fish Osteochilus hassetii (Cyprinidae) equal to 21.2%, Macrognathus siamensis (Mastacembelidea) of 18.3% And found the lowest protein in the meat of Parambassis siamensis (Ambassidae) which is only 3.3%. The protein of some types of fish may differ in quantity due to differences in size, weight, age, source of residence, and season. It is necessary to continue to research the causes of differences in the nutrition of fish, such as the amount of protein in fish, including other important nutrients.